Relação da carga de treino e polimorfismo no gene PPARγ2 (Pro12Ala) com a composição corporal de praticantes de exercícios cíclicos - Silva, Raquel Suelen Brito da (2019)
Introduction: the increasing prevalence of obesity represents a public health problem. Meanwhile, developing effective procedures to promote weight loss is still a challenge to today's scientific knowledge. In intervention studies, there is a limited capacity for exercise, diets and drugs to lose weight and avoid regain. On the other hand, there is an important variability in individual responses to weight loss procedures. Although the obesogenesis / weight loss process is the result of genetic and behavioral factors, as two of these aspects (the training load adopted in procedures aiming at weight loss and the genetic participation in the answers) explains the state of body composition / BC of people is still little investigated. Objective: to verify through a cross-sectional correlational study the relationship of training load and polymorphism in the PPARy2 gene (Pro12Ala) with the BC of 335 practitioners (47.9 ± 12.7 years, 138 men) of cyclic exercises. Methods: the training load was measured by the frequency, duration and speed adopted in the training and the collection of oral cells with subsequent Pro12Ala genotyping by Restriction Fragment Length (PCR-RFLP) technique. BC was measured by electrical bioimpedance. Pearson's correlation test was used to evaluate the relationship of daily caloric expenditure with BC, followed by a multiple linear regression analysis to verify the influence of age, physical activity level (extra training activities) and nutritional intake in BC. To evaluate genotypic influence, an independent t-test or mann-whitney test was performed to evaluate differences between the two groups of genotypes, followed by a chi-square test to evaluate differences between categorical variables (BMI, WHR and PBF). The significance level adopted was p <0.05. Results: the sample practiced 6.9 ± 3.0 sessions / week (119.0 ± 66.5 minutes / session), with daily caloric expenditure of 427.2 ± 355.3 kcal and nutritional intake of 1796.6 ± 657.8 kcal / day. Pearson's test showed a negative association between daily caloric expenditure and BMI (r = -0.23; p <0.05), PGC (r = -0.53; p <0.05) fat mass (r = -0 , 37; p <0.05), WHR (r = -0.31; p <0.05) and visceral fat (r = -0.38; p <0.05). Among men, the correlation was maintained (p <0.05) (except muscle mass) and among women it was maintained for PBF and muscle mass (p <0.05). In the multivariate analysis, it was observed that age (31%; 30%) and nutritional intake (31%; 39%) are influencers of male and female WC, respectively. Genetic analysis showed that Pro/Pro men had a significantly higher BMI than Pro/Ala (p <0.05), the same for total fat mass and visceral fat (p <0.01). In women, Pro/Pro homozygotes had significantly higher BMI than Pro/Ala (p <0.04). The Chi-square test showed that Pro / Pro men showed a significantly higher BMI and PGC distribution (p <0.05; p <0.01, respectively) and women only tended to have a higher Pro / Pro homozygous distribution in the more obese profile (BMI and WHR). Conclusion: training load and Pro12Ala polymorphism were shown to be intervening in BC of physical exercise practitioners, but these factors do not act alone, since age and total caloric intake also participate as predictors.